Kyushoku di Jepang Sebagai Referensi Program Makan Bergizi Gratis di Indonesia - Auliawan, Althaf Gauhar; Harsiwi, Windy (KIRYOKU, 2025)
This study aims to analyze Kyushoku in Japan as a model for the MBG program (free nutritious meal program in Indonesia). Kyushoku is a school lunch program in Japan that has been proven effective in improving children's nutrition and health since 100 years ago. The scope of this research includes the history of Kyushoku, Japanese government policies regarding Kyushoku, and current implementation in Japanese schools. This study uses a literature review, which includes analyzing Japanese government policy documents, related books, and relevant scientific articles. This study collects comprehensive data and information on Kyushoku practices in Japan. The results of this study indicate that Kyushoku in Japan not only focuses on providing nutritious food but also on nutrition education and community involvement in Japan in a sustainable manner. The conclusion of this study shows that the implementation of Kyushoku can be used as a reference for the Indonesian government for the MBG program. In other words, the MBG program in Indonesia is not only expected to be a program that can overcome the problems of malnutrition and stunting, but also has strong regulations, and is positioned as part of sustainable education.